ANALISIS PENGARUH FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL REPORTING MENGGUNAKAN BENISH MODEL [ANALYSIS OF THE EFFECT OF FRAUD PENTAGON ON FRAUDULENT FINANCIAL REPORTING USING THE BENEISH MODEL] - Meiliana Jaunanda; Cindy Tian; Karina Edita; Vivien - (Universitas Pelita Harapan, 2020)
This study discusses the analysis of the influence of Fraud Pentagon on Fraudulent Financial Reporting by using the Beneish Model. Fraud Pentagon as the independent variable in this study, consisting Financial Stability which is proxied by Asset Growth (AGROW), External Pressure is proxied by Leverage (LEV), Opportunities are proxied by Ineffective Monitoring (BDOUT), Related Party Transactions (RPT), Rationalization is proxied by Total Accrual to Total Assets (TATA), Competence is proxied by Changes to the Board of Directors (DCHANGE) and finally Arrogance is proxied by managerial ownership (OSHIP). Fraudulent Financial Reporting as the dependent variable calculated using the Beneish Model. This model uses 8 (eight) calculation ratios, Sales Days in the Receivables Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI), Sales and General Expenditure Administration Index (SGAI), Leverage Index (LVGI), and Total Accruals (TATA). The object of research is the manufacturing companies for the year of 2015-2018 and included in the Indonesia Stock Exchange (IDX), the samples taken for the study are 105 companies using the Purposive Sampling method. The results of this study are (1) Asset Growth (AGROW) and Total Accruals to Total Assets (TATA) are significant towards Fraudulent Financial Reporting. (2) Leverage (LEV), Ineffective Supervision (BDOUT), Related Party Transactions (RPT), Changes to the Board of Directors (DCHANGE) and Managerial Ownership (OSHIP) have no significant effect on False Financial Reporting.Bahasa Indonesia Abstrak: Penelitian ini membahas mengenai analisis pengaruh Fraud Pentagon terhadap Fraudulent Financial Reporting dengan menggunakan Beneish Model. Fraud Pentagon merupakan variabel independen dalam penelitian ini, dimana Financial Stability diproksikan oleh Asset Growth (AGROW), External Pressure diproksikan oleh Leverage (LEV), Opportunity diproksikan oleh Ineffective Monitoring (BDOUT), Related Party Transactions (RPT), Rationalization diproksikan oleh Total Accruals to Total Assets (TATA), Competence diproksikan oleh Change in Board of Director (DCHANGE) dan yang terakhir Arrogance diproksikan oleh kepemilikan manajerial (OSHIP). Variabel dependen menggunakan Fraudulent Financial Reporting yang diukur menggunakan Beneish Model. Model ini menggunakan 8 (delapan) rasio perhitungan yaitu, Days Sales in Receivable Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI), Sales and General Administration Expenses Index (SGAI), Leverage Index (LVGI), dan Total Accrual (TATA). Objek penelitian merupakan perusahaan manufaktur periode 2015-2018 yang tercatat dalam Bursa Efek Indonesia (BEI), sampel yang diambil untuk penelitian sebanyak 105 perusahaan yang didasarkan metode Purposive Sampling. Hasil dari penelitian ini adalah (1) Asset Growth (AGROW) dan Total Accruals to Total Assets (TATA) berpengaruh signifikan terhadap Fraudulent Financial Reporting. (2) Leverage (LEV), Ineffective Monitoring (BDOUT), Related Party Transactions (RPT), Change in Board of Director (DCHANGE) dan Kepemilikan Manajerial (OSHIP) tidak berpengaruh signifikan terhadap Fraudulent Financial Reporting.